Polish nightclubs and bars: Management insights into what customers really want - Heather Skinner; Krzysztof Kubacki; Scott Parfitt; Gloria Moss (Journal for East European Management Studies, 2008)
This research aims to analyse the needs of nightclub and bar customers from emerging and developing Polish market by examining customer preferences towards the servicescape and service offerings provided by such venues. Purposive sampling was used to establish two focus groups within the industry's main target market age group. This data was then subjected to a frequency analysis in SPSS in order to identify those elements that were most preferred by the majority of respondents in Poland. Our findings point to the significant preferences of Polish club-goers, indicating importance of various elements of the servicescape (e.g. gender of clientele, security, seating, location of dance floor and service offering) in influencing customer decisions to enter a venue. – – Diese Studie zielt daraufhin ab, den Bedarf der Kunden von Nightclub und Bars in dem aufstrebenden und sich entwickelnden polnischen Markt anhand der Kundenpräferenzen in Bezug auf Dienstleistungen zu analysieren. Zweckmäßige Stichproben wurden verwendet, um zwei Zielgruppen innerhalb der Hauptalterszielgruppe der Branche zu etablieren. Die Daten wurden dann einer Häufigkeitsanalyse in SPSS unterworfen, um jene Elemente zu identifizieren, die von der Mehrheit der Befragten in Polen am stärksten bevorzugt wurden. Unsere Ergebnisse deuten auf signifikante Vorlieben der polnischen Clubbesucher hin, wobei die Wichtigkeit von verschiedenen Elementen der Dienstleistungen bei der Entscheidungsfindung der Kunden aufgezeigt wird.
Keywords: 650; Servicescape; Nightclubs; bars; Customer attitudes; students